Molecular resolution of a behavioral paradox: sleep and arousal are regulated by distinct acetylcholine receptors in different neuronal types in Drosophila. Issue 7 (25th January 2021) - Dai, Xihuimin; Zhou, Enxing; Yang, Wei; Mao, Renbo; Zhang, Wenxia; Rao, Yi
Abstract: Sleep and arousal are both important for animals. The neurotransmitter acetylcholine (ACh) has long been found to promote both sleep and arousal in mammals, an apparent paradox which has also been found to exist in flies, causing much confusion in understanding sleep and arousal. Here, we have systematically studied all 13 ACh receptors (AChRs) in Drosophila to understand mechanisms underlying ACh function in sleep and arousal. We found that exogenous stimuli-induced arousal was decreased in nAChRα3 mutants, whereas sleep was decreased in nAChRα2 and nAChRβ2 mutants. nAChRα3 functions in dopaminergic neurons to promote exogenous stimuli-induced arousal, whereas nAChRα2 and β2 function in octopaminergic neurons to promote sleep. Our studies have revealed that a single transmitter can promote endogenous sleep and exogenous stimuli-induced arousal through distinct receptors in different types of downstream neurons.